On the age of Early Triassic Tupilakosaurus fauna of Eastern Europe - I. V. Novikov (Известия высших учебных заведений: Геология и разведка)
The composition of Tupilakosaurus fauna is adjusted. Land tetrapod assemblage from the Upper Sukhorechka Subsuite of the Buzuluk Depression is excluded from the fauna. Based on the analysis of all available paleontological (temnospondyl amphibians, phyllopods, palynocomplexes) and paleomagnetic data the age of Tupilakosaurus fauna (and, accordingly, the age of Vokhmian Horizon) is set as Griesbachian (Early Induan). Late Sukhorechka tetrapod assemblage is considered to be Dienerian (Late Induan) in age, compared with a temnospondyl amphibian complex of Myalina kochi beds (uppermost part of the Wordie Creek Formation) of East Greenland and is regarded as an intermediate between the Tupilakosaurus and Benthosuchus faunas.